A Functional Magnetic Resonance Imaging Study of Head Movements in Cervical Dystonia - Prudente, Cecília N.; Stilla, Randall; Singh, Shivangi; Buetefisch, Cathrin; Evatt, Marian; Factor, Stewart A.; Freeman, Alan; Hu, Xiaoping Philip; Hess, Ellen J.; Sathian, K.; Jinnah, H. A. (Frontiers in Neurology, 2016)
Cervical dystonia (CD) is a neurological disorder characterized by abnormal movements and postures of the head. The brain regions responsible for these abnormal movements are not well understood, because most imaging techniques for assessing regional brain activity cannot be used when the head is moving. Recently, we mapped brain activation in healthy individuals using functional magnetic resonance imaging during isometric head rotation, when muscle contractions occur without actual head movements. In the current study, we used the same methods to explore the neural substrates for head movements in subjects with CD who had predominantly rotational abnormalities (torticollis). Isometric wrist extension was examined for comparison. Electromyography of neck and hand muscles ensured compliance with tasks during scanning, and any head motion was measured and corrected. Data were analyzed in three steps. First, we conducted within-group analyses to examine task-related activation patterns separately in subjects with CD and in healthy controls. Next, we directly compared task-related activation patterns between participants with CD and controls. Finally, considering that the abnormal head movements in CD occur in a consistently patterned direction for each individual, we conducted exploratory analyses that involved normalizing data according to the direction of rotational CD. The between-group comparisons failed to reveal any significant differences, but the normalization procedure in subjects with CD revealed that isometric head rotation in the direction of dystonic head rotation was associated with more activation in the ipsilateral anterior cerebellum, whereas isometric head rotation in the opposite direction was associated with more activity in sensorimotor cortex. These findings suggest that the cerebellum contributes to abnormal head rotation in CD, whereas regions in the cerebral cortex are involved in opposing the involuntary movements.